Individual differences in GHB consumption in a new voluntary GHB self-administration model in outbred rats - Casper J. H. Wolf; Marcia Spoelder; Harmen Beurmanjer; Ronald Bulthuis; Arnt F. A. Schellekens; Judith R. Homberg (Psychopharmacology, 2024)
Background and purpose The use of the recreational drug gamma-hydroxybutyric acid (GHB) has increased over the past decade, concomitantly leading to a higher incidence of GHB use disorder. Evidence-based treatment interventions are hardly available and cognitive effects of long-term GHB use remain elusive. In order to study the development of GUD and the causal effects of chronic GHB consumption, a GHB self-administration model is required. Experimental approach Long Evans rats had access to GHB in their home cage according to a two-bottle choice procedure for 3 months. Intoxication and withdrawal symptoms were assessed using an automated sensor-based setup for longitudinal behavioral monitoring. Rats were trained in an operant environment according to a fixed ratio (FR) 1, 2, and 4 schedule of reinforcement. Addiction-like behaviors were assessed through progressive ratio-, non-reinforced-, and quinine-adulterated operant tests. In addition, the novel object recognition test and elevated plus maze test were performed before and after GHB self-administration to assess memory performance and anxiety-like behavior, respectively. Key results All rats consumed pharmacologically relevant levels of GHB in their home cage, and their intake remained stable over a period of 3 months. No clear withdrawal symptoms were observed following abstinence. Responding under operant conditions was characterized by strong inter-individual differences, where only a subset of rats showed high motivation for GHB, habitual GHB-seeking, and/or continued responding for GHB despite an aversive taste. Male rats showed a reduction in long-term memory performance 3 months after home-cage GHB self-administration. Anxiety-like behavior was not affected by GHB self-administration. Conclusion and implications The GHB self-administration model was able to reflect individual susceptibility for addiction-like behavior. The reduction in long-term memory performance upon GHB self-administration calls for further research into the cognitive effects of chronic GHB use in humans.

Modeling and theorizing with agent-based sustainable development - D. Secchi; V. Grimm; D.B. Herath; F. Homberg (Environmental Modelling & Software, 2024)

Evidence of red sensitive photoreceptors in Pygopleurus israelitus (Glaphyridae: Coleoptera) and its implications for beetle pollination in the southeast Mediterranean - J. Martínez-Harms; M. Vorobyev; J. Schorn; A. Shmida; T. Keasar; U. Homberg; F. Schmeling; R. Menzel (Journal of Comparative Physiology A, 2012)

Rapid quantitation of cytomegalovirus DNA in whole blood by a new molecular assay based on automated sample preparation and real-time PCR - Reinhard B. Raggam; Michael Bozic; Helmut J. F. Salzer; Sandra Hammerschmidt; Cordula Homberg; Katharina Ruzicka; Harald H. Kessler (Medical Microbiology and Immunology, 2010)

Adaptations in pre- and postsynaptic 5-HT1A receptor function and cocaine supersensitivity in serotonin transporter knockout rats - Judith R. Homberg; Sietse F. De Boer; Halfdan S. Raasø; Jocelien D. A. Olivier; Mark Verheul; Eric Ronken; Alexander R. Cools; Bart A. Ellenbroek; Anton N. M. Schoffelmeer; Louk J. M. J. Vanderschuren; Taco J. De Vries; Edwin Cuppen (Psychopharmacology, 2008)